Induction Therapy Followed by Surgery for Unresectable Thymic Epithelial Tumours - Wang, Shuai; Jiang, Jiahao; Gao, Jian; Chen, Gang; Fan, Yue; Xu, Bei; Dong, Jihong; Du, Shisuo; Liu, Junzhen; Ding, Jianyong (Frontiers in Oncology, 2022)
Background and Objectives: The treatment of unresectable thymic epithelial tumours (TETs) remains controversial. Here, we present the efficacy and safety of induction therapy followed by surgery for unresectable TET. Methods: Eighty-one patients with unresectable TETs treated with induction therapy followed by surgery were selected from a retrospective review of consecutive TETs from January 2005 to January 2021. Clinicopathological data were analyzed to assess tumour responses, resectability, adverse events, progression-free survival (PFS) and overall survival (OS). Results: Induction therapy produced a major tumour response rate of 69.1%, a tumour response grade (TRG) 1-3 rate of 84.0% and an R0 resection rate of 74.1%. The most common toxic effects were all-grade neutropenia (35.8%) and anaemia (34.6%). The 10-year OS and PFS rates were 45.7% and 35.2%. Multivariate analysis showed that ypTNM stage, ypMasaoka stage, complete resection, and TRG were significant independent prognostic factors. Exploratory research revealed that different induction modalities and downstaging of T, N, M, TNM, or Masaoka classifications did not significantly alter the pooled hazard ratio for survival. Conclusions: Induction therapy followed by surgery is well tolerated in patients with unresectable TETs, with encouraging R0 resection rates. Multimodality management provides good control of tumours for unresectable TET patients.